NINE SPECIES OF APHIDS (HEMIPTERA: APHIDIDAE) NEW TO THE FAUNA OF SERBIA (Acta Entomologica Serbica, 2020)
Nine aphid species (Hemiptera: Aphididae), mainly found in the southeastern part of the country, were determined as new records for Serbia. They belong to three subfamilies: Aphis passeriniana (Del Guercio, 1900); A. podagrariae Schrank, 1801; A. salviae Walker, 1852; Brachyunguis tamaricis (Lichtenstein, 1885); Smiela fusca Mordvilko, 1948; Staticobium limonii Contarini, 1847 and Uroleucon pseudobscurum (Hille Ris Lambers, 1967) from the subfamily Aphidinae; Drepanosiphum oregonensis Granovsky, 1939 from the subfamily Drepanosiphinae and Pterocomma jacksoni Theobald, 1921 from the subfamily Pterocommatinae. With the inclusion of these nine records, a total of 383 aphids have been found so far in Serbia. This represents about 70% of the species of the total aphid fauna expected to be found on plants in Serbia. All species are of Palearctic distribution and seem to be monoecious.